Preparation and structure of phenolic aryliodonium salts. Issue 73 (28th August 2018) - Yoshimura, Akira; Shea, Michael T.; Guselnikova, Olga; Postnikov, Pavel S.; Rohde, Gregory T.; Saito, Akio; Yusubov, Mekhman S.; Nemykin, Victor N.; Zhdankin, Viktor V.
Abstract : para -Hydroxy- and oxy-phenyl(aryl)iodonium salts were prepared and structurally characterized by X-ray crystallography. Abstract : Phenol based aryliodonium salts were prepared by the reaction of [hydroxy(tosyloxy)iodo]arenes with aryl silyl ethers in the presence of trifluoromethanesulfonic acid. Structures of several aryliodonium salts with the hydroxy group in the para -position of the phenyl ring were established by single crystal X-ray crystallography. Under basic conditions, 4-hydroxyphenyl(phenyl)iodonium salts form a dimeric hypervalent iodine(iii ) complex, oxyphenyl(phenyl)iodonium ylidic salt, the solid structure of which was confirmed by X-ray crystallography. Phenolic iodonium salts are potentially useful phenol transfer reagents in reactions with various anionic nucleophiles.